Fear of Falling, Fall Risk and Disability in Patients with Rheumatoid Arthritis - Burcu DUYUR ÇAKIT,; Barış NACIR,; Hatice Rana ERDEM,; Aynur KARAGÖZ,; Meryem SARAÇOĞLU, (Archives of Rheumatology, 2011)
Objectives: This study evaluated frequency of fall, fear of falling (FOF), and fall risk in patients with rheumatoid arthritis (RA) and investigated the relationship of these with functional status, balance, gait, disability, disease activity, and atlantoaxial subluxation (AAS). Patients and methods: Eighty-four female patients with RA and 44 healthy female volunteers were included in the study. Their fall history within the last year was questioned, and any use of an assistive device was recorded. The FOF was assessed using the Falls Efficacy Scale (FES). Tinetti balance and gait tests were performed for the evaluation of balance, gait, and fall risk. The disability in both groups was evaluated with the Health Assessment Questionnaire (HAQ). The disease activity was evaluated with the Chronic Arthritis Systemic Index. The presence of AAS was determined in the patient group using computed tomography imaging. The Beck Depression Inventory (BDI) and the 10-meter walk test were performed in both groups. Results: Twelve (14.3%) subjects in the patient group reported one or more falls within the year. Fifty-six (66.7%) patients described FOF. Anterior AAS was present in 13 (15.4%) patients. According to the Tinetti total score, 33 (39.3%) patients had low, 48 (57.1%) patients had medium, and three (3.6%) patients had high fall risk. The Tinetti total score (R2=0660), HAQ (R2=0.030) and BDI score (R2=0.027) were detected to be the prominent independent risk factors affecting variations in FES scores. No relationship between AAS and fall history, FOF, or disease activity was determined. Conclusion: The most important factors related to the fall risk and FOF were balance and disability level. Because of the increase in the osteoporotic hip fracture risk, the prevention of falls and the reduction of fall risk should be one of the most important rehabilitation goals.